Diversity and species distribution of polychaetes, isopods and bivalves in the Atlantic sector of the deep Southern Ocean - Ellingsen, Kari E.; Brandt, Angelika; Ebbe, Brigitte; Linse, Katrin (Polar Biology, 2007)
We examined deep-sea benthic data on polychaetes, isopods and bivalves from the Atlantic sector of the Southern Ocean. Samples were taken during the expeditions EASIZ II (1998), ANDEEP I and II (2002) (depth: 742-6,348 m). The range between sites varies from 3 to 1,900 km. Polychaetes (175 species in total) and isopods (383 species) had a high proportion of species restricted to one or two sites (72 and 70%, respectively). Bivalves (46 species) had a higher proportion of species represented at more sites. Beta diversity (Whittaker and Jaccard) was higher for polychaetes and isopods than for bivalves. The impact of depth on species richness was not consistent among groups; polychaetes showed a negative relationship to depth, isopods displayed highest richness in the middle depth range (2,000-4,000 m), whereas bivalves showed no clear relationship to depth. Species richness was not related to latitude (58-74 degrees S) or longitude (22-60 degrees W) for any group.
Keywords: Sørishavet; biodiversitet; flerbørstemarker; isopoder; marin biologi; muslinger; skjell; tanglus

Polychètes pélagiques des expéditions norvégiennes antarctiques de la "Norvegia" 1927-1928, 1928-1929 et 1930-1931 - Støp-Bowitz, Carl (Dybwad, 1949)
Keywords: Norvegia ekspedisjoner; Sørishavet; flerbørstemarker; leddormer; marin biologi